Substrate‐dependent risk stratification for implantable cardioverter defibrillator therapies using cardiac magnetic resonance imaging: The importance of T1 mapping in nonischemic patients. (9th June 2017) - Claridge, Simon; Mennuni, Silvia; Jackson, Thomas; Behar, Jonathan M.; Porter, Bradley; Sieniewicz, Benjamin; Bostock, Julian; O'Neill, Mark; Murgatroyd, Francis; Gill, Jaswinder; Carr‐White, Gerald; Chiribiri, Amedeo; et al.
Abstract: Introduction: The role of implantable cardioverter defibrillators (ICDs) in nonischemic cardiomyopathy is unclear and better risk‐stratification is required. We sought to determine if T1 mapping predicts appropriate defibrillator therapy in patients with nonischemic cardiomyopathy. We studied a mixed cohort of ischemic and nonischemic patients to determine whether different cardiac magnetic resonance (CMR) applications (T1 mapping, late gadolinium enhancement, and Grayzone) were selectively predictive of therapies for the different arrhythmic substrates. Methods and results: We undertook a prospective longitudinal study of consecutive patients receiving defibrillators in a tertiary cardiac center. Participants underwent CMR myocardial tissue characterization using T1 mapping and conventional CMR scar assessment before device implantation. QRS duration and fragmentation on the surface electrocardiogram were also assessed. The primary endpoint was appropriate defibrillator therapy. One‐hundred thirty patients were followed up for a median of 31 months (IQR ± 9 months). In nonischemic patients, T1 _native was the sole predictor of the primary endpoint (hazard ratio [HR] 1.12 per 10 millisecond increment in value [95% confidence interval [CI] 1.04–1.21; P ≤ 0.01]). In ischemic patients, Grayzone _2SD‐3SD was the strongest predictor of appropriate therapy (HR 1.34 per 1% left ventricular increment in value [95% CI 1.03–1.76; P = 0.03]). QRS fragmentation correlated well with myocardial scar core (receiver operating characteristic area under the curve [ROC AUC] 0.64; P = 0.02) but poorly with T1 _native (ROC AUC 0.4) and did not predict appropriate therapy. Conclusions: In the medium–long term, T1 _native mapping was the only independent predictor of therapy in nonischemic patients, whereas Grayzone was a better predictor in ischemic patients. These findings suggest a potential role for T1 _native mapping in the selection of patients for ICDs in a nonischemic population.